Numerical simulations of human respiratory flows: a review - Anna Lancmanová; Tomáš Bodnár (Discover Applied Sciences)
Abstract This paper presents an overview of selected past and recent works on mathematical modeling and numerical simulations in respiratory fluid mechanics. The primary aim of this review is to systematically review, categorize and assess the state-of-the-art numerical approaches used to model the fluid flow in the respiratory system, highlighting the known strengths and limitations of each approach. In addition, the paper outlines existing gaps in the current methodologies and identifies trends which may lead to potential future advancements in the field. The structure of the paper reflects the historical background and current developments in the medical imaging and experimental techniques, that have significantly improved the characterization of human airway geometries and the ability to represent realistic flow regimes in recent years. The mathematical models used for numerical simulations are briefly introduced and discussed, focusing on the incompressible and compressible Navier–Stokes equations and Lattice Boltzmann models. An important part of the paper is dedicated to the overview of turbulence modeling approaches used in respiratory flows modeling. Emphasis is on the current trends and limitations in turbulence modeling in various applications to respiratory problems. In addition to common respiratory fluid mechanics, two additional applications are discussed in greater detail, the respiratory aerosols and fluid–structure interaction problems.